Dynamic analysis of a hydraulic motor drive with variable inertia flywheel. (July 2020) - Kushwaha, Prabhakar; Ghoshal, Sanjoy K; Dasgupta, Kabir
A flywheel is presented in this article, which can adaptively generate variable inertia in response to the application requirements in a hydraulic drive. The said flywheel consists of four sliders in the guide track of a host flywheel frame which change its position as the rotational speed of the flywheel varies. The varying distance between the slider and the center of rotation leads to a variable inertial mass. This passive inertial mass has a potential to reduce the speed fluctuations of the drive. A comparative study has been made on the effects of the variable inertia flywheel on the hydraulic motor speed fluctuations with that of the fixed inertia flywheel. In this respect, a bond graph model of the hydraulic motor drive with the variable inertia flywheel and the fixed inertia flywheel is developed to analyze their performances. The variable inertia generated by the variable inertia flywheel reduces the hydraulic motor speed fluctuations in response to the changes in the excitation inputs. The tests were conducted to validate the model for step change in speed of the hydraulic motor. The test results of the hydraulic motor speed response are found in good agreement with the predicted response. The proposed design of the flywheel reduces the peak speed of the hydraulic motor that enhances the reliability and performance of the drive.